Geotechnical Assessment of Foundation Stability for Preserving the Agrippa Monument at the Acropolis of Athens - Vassilis Marinos; Georgios Prountzopoulos; Dimitra Papouli; Dionisia Michalopoulou; Vassiliki Eleftheriou (Sensors)
This study focuses on the geotechnical evaluation of the foundation conditions of the Agrippa Monument at the Acropolis of Athens, aiming to propose interventions to improve stability and reduce associated risks. The assessment reveals highly uneven foundation conditions beneath the monument. A thorough collection of bibliographic references and geotechnical surveys was conducted, classifying geomaterials into engineering-geological units and evaluating critical parameters for geotechnical design. Geotechnical models were developed and 3D finite element analyses were performed. The qualitative evaluation of the foundation under static conditions indicates no immediate risk of failure, as no accelerated movement has been observed and the monument’s tilt remains well below critical values. Time-dependent settlements are not expected from any clay layers in the artificial fills. However, further soil compaction could occur due to seismic events, water action (causing erosion or voids), or changes in the monument’s weight or tilt under static conditions. The study also proposes instrumental monitoring, foundation soil improvement, and water management strategies to enhance the monument’s stability and mitigate potential risks.